Letter (copy) : Guiseppe Gatti - Citrine, Walter, 1887-1983
027-0049-001 INTERNATIONAL. WMC/EAB. 30th October 1939. Miss E. Sylvia Pankhurst, "West Dene", 3, Charteris Road, Woodford Green, ESSEX. Dear Miss Pankhurst, GUISEPPE GATTI. Thank you for your letter of the 26th inst., regarding the case of Guiseppe Gatti, a Spanish Refugee, now in Brixton Prison. I understand from the Labour Party that they already have the matter in hand and are in contact with the Home Office. If you would like further information about the case, perhaps you will be good enough to telephone to Mr. W. Gillies, Labour Party International Department. Yours sincerely, General Secretary. 292/946/27/49